Potential Local Ingredients from Purple Sweet Potato For Weaning Food Using Ultrasound Modified Process - Riani, Ira Gusti; Utami, Aldilla Sari; Handayani, Marta Tika; Khairunnisa, Eka Nurriza (Program Pascasarjana Universitas Sriwijaya, 2024)
Purple sweet potato is a source of carbohydrates that can be used as a substitute for rice. Besides its sweet taste, it has a striking color that comes from anthocyanins. Purple sweet potato is a rich potential local food, it was cheaper. Purple sweet potato powder is a practice innovation. It was a semi-finished product that is instant and easy to use. One of its uses is for weaning food. It must be high nutrition, higyenic and safe. Physical modification is considered safer because it does not use chemicals and leaves no chemical residue. This study used a Factorial Completely Randomized Design with 6 treatments (a combination between purple sweet potato starch and rice flour). Parameters observed were viscosity, bulk density, time rehydration, and water absorbtion. The best treatment was F5 (100% modified starch and 0% rice flour) with 0.50 g/mL bulk density, 135.40% water absorbtion, 136.67 dPas and 31.70 s rehydration time.